On shape parameter α -based approximation properties and q-statistical convergence of Baskakov-Gamma operators - Chen, Ming Yu; Md Nasiruzzaman; Mursaleen, Mohammad Ayman; Rao, Nadeem; Kilicman, Adem (Hindawi, 2022)
We construct a novel family of summation-integral-type hybrid operators in terms of shape parameter α ∈ [0, 1] in this paper. Basic estimates, rate of convergence, and order of approximation are also studied using the Korovkin theorem and the modulus of smoothness. We investigate the local approximation findings for these sequences of positive linear operators utilising Peetre’s K-functional, Lipschitz class, and second-order modulus of smoothness. The approximation results are then obtained in weighted space. Finally, for these operators q-statistical convergence is also investigated.